Anti Human Trafficking: The Salvation Army and Advocacy - Brooke, Petra (Diaconia, 2022)
This article explores The Salvation Army’s (TSA) faith-based modern slavery and human trafficking work by reviewing TSA’s foundational and strategic documents, with a particular investigation of the TSA’s "theology of holy life". This article explores how TSA conducts its work and how theology and social actions, in this case anti human trafficking work, are interconnected. Using document analysis on theological documents, practice guiding documents and strategic documents from the TSA, the article presents a case study on two levels: TSA as a case and TSA in Norway as a case within a case. The article enables better understanding of the link between TSA’s theology and the consequences of the integrated mission of TSA.